Extraction of ascorbic acid from fresh pineapple - Asdarina, Yahya (2006)
Pineapple fruits have a high concentration of ascorbic acid, nowadays everybody know it as Vitamin C in their composition. Today, ascorbic acid is one important supplement to take care of health. . There are a lot of benefits that can get from ascorbic acid. Before the extraction of ascorbic acid from fresh pineapple, the fresh pineapple was cuted and cleaned. Pineapple needed to blend and the filtered. After that, the sample is being mix with the solvent extraction, which is .0.02 M potassium phosphate, pH 2.5 by phosphoric acid : acetonitrile (98 : 2.). The mixers then sonicated in ultrasonic extraction follow the time that are determined. There are two objectives in this research, first to determine the optimum extraction time. The parameters that will use are 10 minutes, 20 minutes and 30 minutes. Then the other one is to determine the optimum amount of sample. The parameters that used is 20 ml, 40 ml, and 60 ml of sample. Then the samples are filtered again before analysis. High Performance Liquid Chromatography (HPLC) was used to analyze where there are contain or not ascorbic acid in fresh pineapple. The HPLC method was used to developed and validated for determining the amount of ascorbic acid in fresh pineapple. The mobile phase that used in HPLC is 0.02 M potassium phosphate, pH 2.5 by phosphoric acid and acetonitrile. Ascorbic acid was determined at range one to two minutes and gets two peaks. The first peak is l ascorbic acid and the second one is dehydroascorbic acid (DHA). This research finally obtained the objective of the